The Effect of Compliance With Wearing Appropriate Protective Personal Equipment With Exposure Risk on The Incidence of Occupational Accidents - Sadat, Lubna Anwar; Najie, Ilyu 'Ainun; Afrizal, Adheelah Rachmah (Jurnal Health Sains, 2023)
Work accidents are one of the problems that often occur in the workplace. Work accidents can cause material and non-material losses, both for workers, companies, and society. One of the factors that can cause work accidents is workers' non-compliance in using personal protective equipment (PPE). The purpose of this study was to analyze the effect of compliance with the use of PPE in accordance with the risk of exposure to the incidence of work accidents. The research method used in this research is quantitative research. The data collection techniques used in this study were questionnaires and literature studies. The data that has been collected is then analyzed using the help of the SPSS program. The results showed that compliance with the use of PPE in accordance with the risk of exposure had a significant effect on the incidence of work accidents. Workers who are obedient in using PPE have a lower risk of work accidents compared to workers who are not obedient in using PPE